2009
DOI: 10.2337/db09-1128
|View full text |Cite|
|
Sign up to set email alerts
|

Insulin Causes Hyperthermia by Direct Inhibition of Warm-Sensitive Neurons

Abstract: OBJECTIVETemperature and nutrient homeostasis are two interdependent components of energy balance regulated by distinct sets of hypothalamic neurons. The objective is to examine the role of the metabolic signal insulin in the control of core body temperature (CBT).RESEARCH DESIGN AND METHODSThe effect of preoptic area administration of insulin on CBT in mice was measured by radiotelemetry and respiratory exchange ratio. In vivo 2-[18F]fluoro-2-deoxyglucose uptake into brown adipose tissue (BAT) was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 17 publications
12
88
0
Order By: Relevance
“…Central injection of insulin into the PO/AH of the hypothalamus induced a dose-dependent increase in BAT thermogenesis and fatty acid oxidation in mice ( 80 ). Insulin is known to inhibit NPY/AgRP neurons and to stimulate POMC neurons ( 80 ). As these neurons are also involved in mediating BAT activity and thermogenesis (as described above), the effect of insulin on BAT thermogenesis is likely mediated by either increased MC4R activation or decreased NPY activation.…”
Section: Summary Clinical Implications and Future Perspectivesmentioning
confidence: 94%
See 1 more Smart Citation
“…Central injection of insulin into the PO/AH of the hypothalamus induced a dose-dependent increase in BAT thermogenesis and fatty acid oxidation in mice ( 80 ). Insulin is known to inhibit NPY/AgRP neurons and to stimulate POMC neurons ( 80 ). As these neurons are also involved in mediating BAT activity and thermogenesis (as described above), the effect of insulin on BAT thermogenesis is likely mediated by either increased MC4R activation or decreased NPY activation.…”
Section: Summary Clinical Implications and Future Perspectivesmentioning
confidence: 94%
“…Central injection of insulin into the PO/AH of the hypothalamus induced a dose-dependent increase in BAT thermogenesis and fatty acid oxidation in mice ( 80 ). Insulin is known to inhibit NPY/AgRP neurons and to stimulate POMC neurons ( 80 ).…”
Section: Summary Clinical Implications and Future Perspectivesmentioning
confidence: 99%
“…In addition, several circulating factors such as insulin, leptin and GLP-1 have been identified to promote thermogenesis through targeting hypothalamus neurons and regulating activity of SNS (Shimizu et al 1987, Rahmouni & Morgan 2007, Sanchez-Alavez et al 2010, Harlan et al 2011, Lockie et al 2012, Beiroa et al 2014, Dodd et al 2015 (Fig. 3).…”
Section: Regulation Of Non-shivering Thermogenesismentioning
confidence: 99%
“…Projection of warm-sensitive neurons outside of the POA remains to be investigated. Suggesting a role of warmsensitive POA neurons in metabolic regulation, a recent study reported that a direct action of insulin on warm-sensitive POA neurons reduces their firing rates, and injection of insulin into the POA elicits a rise in body core temperature involving BAT thermogenesis (144).…”
Section: Central Thermosensation For Body Temperature Regulationmentioning
confidence: 99%